2016
DOI: 10.1007/s10498-016-9300-8
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Carbon Mineralization and Nutrient Turnover in a Scottish Sea Loch: An Integrative In Situ Study

Abstract: Based on in situ microprofiles, chamber incubations and eddy covariance measurements, we investigated the benthic carbon mineralization and nutrient regeneration in a *65-m-deep sedimentation basin of Loch Etive, UK. The sediment hosted a considerable amount of infauna that was dominated by the brittle star A. filiformis. The numerous burrows were intensively irrigated enhancing the benthic in situ O 2 uptake by *50 %, and inducing highly variable redox conditions and O 2 distribution in the surface sediment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 105 publications
2
22
0
Order By: Relevance
“…Benthic oxygen uptake provides a good proxy for benthic mineralisation (Glud et al 2016;Jahnke et al 2000;Woulds et al 2007), however spatial and temporal variability of oxygen dynamics may present a bias in interpretation if careful consideration is not given to the methodology used and caveats of each approach, e.g. incubations favour diffusive processes so may lead to over or underestimation in permeable sediments (Lohse et al 1996;Tengberg et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Benthic oxygen uptake provides a good proxy for benthic mineralisation (Glud et al 2016;Jahnke et al 2000;Woulds et al 2007), however spatial and temporal variability of oxygen dynamics may present a bias in interpretation if careful consideration is not given to the methodology used and caveats of each approach, e.g. incubations favour diffusive processes so may lead to over or underestimation in permeable sediments (Lohse et al 1996;Tengberg et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Benthic oxygen uptake is often used as a robust proxy for total benthic mineralisation (Glud et al 2016;Jahnke et al 2000;Stahl et al 2004b), and this method is particularly applicable in cohesive sediments (Glud 2008). The rate of oxygen uptake, or consumption, is determined by the type of sediment; the presence, quality (labile vs refractory) and quantity of organic matter in the sediment; and the organisms that live on and within the sediment (from microorganisms and meiofauna to macrofauna).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using similar in situ methods, Reimers et al (2016) provide new insights into the dynamics of benthic respiration by measuring oxygen exchange rates in mid-shelf sediments off the Oregon coast. Glud et al (2016) also use these in situ and other methods to understand carbon mineralization and nutrient turnover as a result of oxygen uptake and exchange across the water sediment interface. Organisms influence element cycling across the water-sediment interface via bioturbation, which has two major components [bio-mixing (solid particle transport) and bio-irrigation (enhance solute transport)] that Van de Velde and Meysman (2016) describe with a reactive transport model to further our understanding of iron and sulfur cycling.…”
Section: Contributions By Colleagues To This Special Issuementioning
confidence: 99%
“…Biogeochemical models mostly consider bio-irrigation (biological enhancement of solute transfer) as a factor enhancing the diffusion coefficient (Blackford, 1997;Reed et al, 2011), resulting in a thicker oxic layer near the sediment surface. However, the transport of oxygen (and other solutes) will likely not occur homogenously, rather being concentrated along the network of burrows (Glud et al, 2016), which become an extension of the oxic-anoxic interface. It has been shown that burrowing activity of benthic macrofauna can lead to as much as 400% increase in denitrification rates (Gilbert et al, 1998;Webb and Eyre, 2004), mostly due to the high rates of nitrification occurring within the burrows (Howe et al, 2004).…”
Section: Biological Transport and Small-scale Heterogeneitymentioning
confidence: 99%